Peleburan Realitas Nyata dan Maya: Hoax Menjadi Konsumsi Masyarakat Global - agustina, dwi (Jurnal Sosiologi Agama, 2018)
The emergence of globalization show the existence of two sides to the light and the dark. The increasing of digital information technology becomes one of the obvious facts about the bright side of globalization. However, globalization in fact also provides a dark side in the era of increasingly advanced technology, one of which is the emergence of news hoax. Social media has become a new space for people to express their opinions without any social restrictions. The result between the real and the no longer becomes unlimited. This paper wants to analyze critically about the emergence of news hoax consumed by the public, with data collection used is literature study. News hoaxes are increasingly flooding the virtual world is now a cultural product in the consumption by the wider community. With just one click, hoax can spread all over the world. Thus, the virtual world becomes a public space that people consume to bullying and disseminate content that is not true. Keywords: social media, hoax, consumption culture, globalization